School student administration system - Mohd Ridhuan, Hussain (2013)
In this paper, a system that can manage the registration process of the students, convey information about the school activities by sending SMS to their parent and student attendance will be record automatically. Student’s management in an organization is very complex. When talking about learning, student registration is a matter of a compulsory and usually taking registration takes a long time to fill out many forms. In addition, many letters will be given to the parents via students. Due this reason, a system was designed to overcome this problem. This system to register students, convey information about school activities by sending SMS. No longer need all the forms, letters statements, stationery and a list of students to record student attendance. In fact, this system can replace the old system to a more systematic and computerized.